Mechanisms contributing to persistently activated cell phenotypes in pulmonary hypertension - Hu, Cheng‐Jun (J Physiol, 2018)
Chronic pulmonary hypertension (PH) is characterized by the accumulation of persistently activated cell types in the pulmonary vessel exhibiting aberrant expression of genes involved in apoptosis resistance, proliferation, inflammation and extracellular matrix (ECM) remodelling. Current therapies for PH, focusing on vasodilatation, do not normalize these activated phenotypes. Furthermore, current approaches to define additional therapeutic targets have focused on determining the initiating signals and their downstream effectors that are important in PH onset and development. Although these approaches have produced a large number of compelling PH treatment targets, many promising human drugs have failed in PH clinical trials. Herein, we propose that one contributing factor to these failures is that processes important in PH development may not be good treatment targets in the established phase of chronic PH. We hypothesize that this is due to alterations of chromatin structure in PH cells, resulting in functional differences between the same factor or pathway in normal or early PH cells versus cells in chronic PH. We propose that the high expression of genes involved in the persistently activated phenotype of PH vascular cells is perpetuated by an open chromatin structure and multiple transcription factors (TFs) via the recruitment of high levels of epigenetic regulators including the histone acetylases P300/CBP, histone acetylation readers including BRDs, the Mediator complex and the positive transcription elongation factor (Abstract figure). Thus, determining how gene expression is controlled by examining chromatin structure, TFs and epigenetic regulators associated with aberrantly expressed genes in pulmonary vascular cells in chronic PH, may uncover new PH therapeutic targets. [Image: see text]